Propagação superluminal de pulsos com suporte compacto suave em circuitos eletrônicos - Souza, Samuel Teixeira de (2010)
In this work, using pulses based on functions with compact support and perfectly smooth infinitely differentiable zero intensity non analytical points, We demonstrated numerically and experimentally, a new approach to model information propagating through an electronic circuit producing negative group delays. Here, the information is associated to smooth non analytical points present in the leading edge of a pulse. The pulse or any of its derivatives does not present any discontinuity, in direct contradiction with standard literature that claims the necessity of a discontinuous front or a discontinuous derivative in order to code information. Our results show that the non analytical point in the pulse’s leading edge propagates with a velocity equal to velocity of light in vacuum c for all investigated cases. We find that the causality influence on the pulse propagation through a superluminal system, producing pulse steepening and even breakup. Our results contribute to a better undestanding of information propagation and shed light over perhaps one of the last misconceptions regarding superluminality and the speed of information